Characterization of Mg-rich natural serpentine clay mineral and removal of reactive blue 19 from aqueous solutions - Değermenci, Gökçe Didar; Değermenci, Nejdet; Emin, Nuray; Aşıkuzun, Elif (EQA - International Journal of Environmental Quality, 2022)
The present study assessed the use of serpentine clay as adsorbent to remove the anionic dye agent of Reactive Blue 19 (RB19) from aqueous solutions. Firstly, serpentine clay minerals were characterized using different instrumental techniques like XRD, FTIR, SEM, TGA, XRF and BET analysis. As a result of characterization, the clay sample was determined to be serpentine group and it contained antigorite as dominant mineral type. Later, adsorption studies were performed and the effects of initial pH, adsorbent dosage, initial dye concentration and temperature on RB19 removal were investigated. The experimental results determined the highest adsorption capacity was obtained as 44.8 mg/g with initial RB19 concentration of 200 mg/L, temperature 25°C, adsorbent concentration 2 g/L and pH 7. According to isotherm results, the Langmuir isotherm model was more suitable to explain adsorption of RB19 on serpentine compared to the Freundlich isotherm model. Additionally, adsorption data indicate the pseudo-second-order kinetic model is a better fit rather than the pseudo-first-order kinetic model.

EQA - International Journal of Environmental Quality, Vol. 47 (2022)